Effects of benralizumab in a population of patients affected by severe eosinophilic asthma and chronic rhinosinusitis with nasal polyps: a real life study - Santomasi, Carla; Buonamico, Enrico; Dragonieri, Silvano; Iannuzzi, Lucia; Portacci, Andrea; Quaranta, Nicola; Carpagnano, Giovanna Elisiana (Acta Biomedica Atenei Parmensis, 2023)
Background. Chronic rhinosinusitis with nasal polyps (CRSwNP) is a frequent comorbidity in severe eosinophilic asthma (SEA), which may contribute to the loss of asthma control. CRSwNP and SEA share a T2-mediated mechanism and the use of some anti-asthma monoclonal antibodies has recently been extended to CRSwNP. Unlike dupilumab and omalizumab, benralizumab approval for CRSwNP is ongoing. We aimed to evaluate the efficacy of benralizumab efficacy on SEA and on CRSwNP in patients affected by both pathologies in a real life setting.Methods. 17 patients affected by both SEA and CRSwNP participated to our study. At baseline (T0) and at one year after benralizumab initiation (T1), all participants underwent  spirometry, exhaled nitric oxide (FeNO), Asthma Control Test (ACT), nasal endoscopy with Nasal Polyp Score (NPS), nasal cytology and Sino-Nasal Outcome Test 22 (SNOT 22).The continuous oral corticosteroid therapy (OCS), the number of year exacerbations and the need for sinus surgery were also evaluated  for each patient.Results. At T1, a marked reduction of SNOT-22, NPS, nasal eosinophils and neutrophils count were shown compared to T0. Moreover, at T1 ACT was significantly increased and FeNO, exacerbations/year and mean OCS dosage were significantly reduced compared to T0.Conclusions. Our real-life study demonstrates the efficacy of benralizumab not only on SEA but also on nasal cytology and on nasal polyposis, confirming that patients affected by both SEA and CRSwNP may receive a considerable benefit from anti-IL5 receptor, treating both the comorbidities at once.